Refractory acute suppurative thyroiditis secondary to pyriform sinus fistula - Jee Hyue Seo; Yong Hoon Park; Sei Won Yang; Hyun Young Kim (Korean Society of Pediatric Endocrinology, 2014)
Acute suppurative thyroiditis is a rare disease because the thyroid gland is remarkably resistant to infection. We present a 2-year-old girl with refractory acute suppurative thyroiditis due to a pyriform sinus fistula (PSF). She complained of fever and painful anterior neck swelling. Her condition did not completely improved by multiple parenteral antibiotics along with incision and drainage. Barium esophagogram to detect PSF demonstrated no specific finding. Computed tomography scan showed air bubble superior to the left thyroid gland which indicated a possible fistula connected to the pyriform sinus. An intraoperative laryngoscopy revealed a 2-mm-sized fistula opening. The fistula was successfully treated by chemocauterization with trichloroacetic acid.